Tanshinone IIA Has a Potential Therapeutic Effect on Kawasaki Disease and Suppresses Megakaryocytes in Rabbits With Immune Vasculitis - Hui Chen; Huiying Shu; Weiqing Su; Bo Li; Bo Li; Hua Zhang; Liang Li; Chao Lin; Wenfang Yi; Xiao-Yong Zhan; Chun Chen; Xiaojing Li; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and ObjectiveIt is urgent to find out an alternative therapy for Kawasaki disease (KD) since around 20% patients are resistant to intravenous immunoglobulin (IVIG) or aspirin. Tanshinone IIA is the active component of the traditional Chinese medicine Danshen (Salvia miltiorrhiza), which has anti-inflammatory and anti-platelet properties; however, whether or not tanshinone IIA has a therapeutic effect on KD remains unclear. Therefore, the present study aimed to examine the effect of tanshinone IIA on KD patients and rabbits with immune vasculitis, and to identify the potential mechanisms with special emphasis on megakaryopoiesis and megakaryocytic apoptosis.MethodsKawasaki disease patients were recruited and prescribed with tanshinone IIA in the absence or presence of aspirin and IVIG, and the inflammatory responses and platelet functions were determined. Megakaryocytes (MKs) isolated from rabbits with immune vasculitis and human megakaryocytic CHRF-288-11 cells were treated with tanshinone IIA to examine the colony forming unit (CFU) and apoptosis, respectively. Microarray assay was conducted to identify potential targets of tanshinone IIA-induced apoptosis.ResultsTanshinone IIA reduced the serum levels of C-reactive protein (CRP), interleukin (IL)-1β, IL-6, and P-selectin in KD patients; such inhibitory effect was more significant compared to aspirin and IVIG. It also dose-dependently lowered the levels of tumor necrosis factor (TNF)-α and IL-8 in peripheral blood mononuclear cells isolated from KD patients. In rabbits with immune vasculitis, tanshinone IIA significantly reduced the serum levels of proinflammatory cytokines and platelet functions. In addition, tanshinone IIA significantly decreased the number of bone marrow MKs and inhibited the Colony Forming Unit-Megakaryocyte (CFU-MK) formation. In human megakaryocytic CHRF-288-11 cells, tanshinone IIA induced caspase-dependent apoptosis, probably through up-regulating TNF receptor superfamily member 9 (TNFRSF9) and the receptor (TNFRSF)-interacting serine/threonine-protein kinase 1 (RIPK1), which may contribute to its anti-platelet and anti-inflammatory properties.ConclusionTanshinone IIA exerts better anti-inflammatory and anti-platelet effects in treating KD patients than aspirin and IVIG. It attenuates immune vasculitis likely by inhibiting IL-mediated megakaryopoiesis and inducing TNFRSF9/RIPK1/caspase-dependent megakaryocytic apoptosis. The findings therefore suggest that tanshinone IIA may be a promising alternative therapy for the treatment of KD.